Comparison of multilocus sequence types found among North American isolates of Mycoplasma bovis from cattle, bison, and deer, 2007–2017. (November 2019) - Register, Karen B.; Jelinski, Murray D.; Waldner, Matthew; Boatwright, William D.; Anderson, Tavis K.; Hunter, David L.; Hamilton, Robert G.; Burrage, Pat; Shury, Todd; Bildfell, Robert; Wolff, Peregrine L.; Miskimins, Dale; et al.
A prior multilocus sequence typing (MLST) study reported that Mycoplasma bovis isolates from North American bison possess sequence types (STs) different from those found among cattle. The 42 bison isolates evaluated were obtained in 2007 or later, whereas only 19 of 94 (~20%) of the available cattle isolates, with only 1 from North America, were from that same time. We compared STs of additional, contemporary, North American cattle isolates with those from bison, as well as isolates from 2 North American deer, all originating during the same timeframe, to more definitively assess potential strain-related host specificity and expand our understanding of the genetic diversity of M. bovis . From 307 isolates obtained between 2007 and 2017 (209 from cattle, 96 from bison, 2 from deer), we identified 49 STs, with 39 found exclusively in cattle and 5 exclusively in bison. Four STs were shared between bison and cattle isolates; one ST was found in cattle and in a deer. There was no clear association between ST and the health status of the animal of origin. An MLST-based phylogeny including 41 novel STs identified in our study reveals that STs found in bison fall within several divergent lineages that include STs found exclusively in cattle.